2017
DOI: 10.3389/fnagi.2017.00026
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cystatin C and High-Density Lipoprotein Are Important Biomarkers of Alzheimer’s Disease and Vascular Dementia: A Cross-Sectional Study

Abstract: Objectives: Cystatin C (Cys C) and high-density lipoprotein (HDL) play critical roles in neurodegenerative diseases, such as dementia, Alzheimer’s disease (AD) and vascular dementia (VaD). However, whether they can be used as reliable biomarkers to distinguish patients with dementia from healthy subjects and to determine disease severity remain largely unknown.Methods: We conducted a cross-sectional study to determine plasma Cys C and HDL levels of 88 patients with dementia (43 AD patients, 45 VaD patients) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 40 publications
2
28
1
Order By: Relevance
“…Generally speaking, weight loss and malnutrition is commonly observed in neurodegenerative diseases, such as PD, AD, and amyotrophic lateral sclerosis (ALS). Present evidence suggests that inflammation and mitochondrial impairment play an important role in neurodegenerative diseases (Xu et al, 2013 ; Wei et al, 2016 ; Wang et al, 2017 ), which may be also responsible for energy balance (Aziz et al, 2008 ). In the context of PD, our basic understanding of mechanism of weight loss and malnutrition is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, weight loss and malnutrition is commonly observed in neurodegenerative diseases, such as PD, AD, and amyotrophic lateral sclerosis (ALS). Present evidence suggests that inflammation and mitochondrial impairment play an important role in neurodegenerative diseases (Xu et al, 2013 ; Wei et al, 2016 ; Wang et al, 2017 ), which may be also responsible for energy balance (Aziz et al, 2008 ). In the context of PD, our basic understanding of mechanism of weight loss and malnutrition is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, deepening of knowledge on molecular mechanisms underlying PD insurgence and progression is crucial for discovering innovative molecular targets useful for developing more effective therapeutic strategies. In the last years, numerous studies have been published, that aimed to identify innovative PD biomarkers, also useful as therapeutic targets, and to demonstrate the neuroprotective role of endogenous and exogenous molecules ( Chen et al, 2015 ; Price et al, 2015 ; Wang et al, 2017 ; Zou et al, 2017 )…”
Section: Introductionmentioning
confidence: 99%
“…Except PKC-α, miR-330-3p has many other targets that may be relevant, such as Cystatin C and AKT3. Study showed cystatin C was involved in the process of VEGF-inducing angiogenesis and enhanced neuronal autophagy in neurovascular units (Wang et al, 2017 ; Zou et al, 2017 ). PI3K/Akt signaling is an important pathway for autophagy and has neuroprotective effects (Xu et al, 2013 ; Ma et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%